Work Ethics and Quality Workplace: An Observation from the Conventional and Islamic Application - Khatijah Othman (Universiti Sains Islam Malaysia, 2024)
In general, good work ethics is always being assumed as a good conduct of employees’ behavior within the workplace. However, Islamic work ethics having much deeper values and goals to achieve both in this world and hereafter in comparison to the conventional work ethics. Whilst Islamic workplace quality, on the other hand, differ from what the conventional meant. Therefore, this paper intends to highlight the meaning, characteristics, and the application of Islamic work ethics in the organization. Through this study, the researcher at the same time addressed the meaning of Islamic workplace quality and analyze its relations to how Islamic ethical conduct helps to improvise and realize the existence of Islamic workplace quality. This study is based on the secondary resources gained from library research and web based journals and articles. The finding of this study shows that the workplace quality can be built with the essence of Islamic akhlaq and adab (ethical good conduct) which contain the spirits, understandings and practices of struggle and responsibility, knowledge development and knowhow, excellence at work, justice, truthfulness, trustworthiness and amanah. The current conceptual analysis is hoped to be able to contribute to the understanding of the concept of Islamic work ethics and its applications in the Islamic organization, especially to meet the vision on realizing the Islamic workplace quality in the contemporary highly competitive economy.